Components of the acoustic swallowing signal: Preliminary study - Spadotto, André Augusto; Gatto, Ana Rita [UNESP]; Cola, Paula Cristina [UNESP]; Silva, Roberta Gonçalves da [UNESP]; Schelp, Arthur Oscar [UNESP]; Domenis, Danielle Ramos; Dantas, Roberto Oliveira (FapUNIFESP (SciELO), 2012)
Purpose: To analyze the components of the acoustic signal of swallowing using a specific software. Methods: Fourteen healthy subjects ranging in age from 20 to 50 years (mean age 31±10 years), were evaluated. Data collection consisted on the simultaneous capture of the swallowing audio with a microphone and of the swallowing videofluoroscopic image. The bursts of the swallowing acoustic signal were identified and their duration and the interval between them were later analyzed using a specific software, which allowed the simultaneous analyses between the acoustic wave and the videofluoroscopic image. Results: Three burst components were identified in most of the swallows evaluated. The first burst presented mean time of 87.3 milliseconds (ms) for water and 78.2 for the substance. The second burst presented mean time of 112.9 ms for water and 85.5 for the pasty substance. The mean interval between first and second burst was 82.1 ms for water and 95.3 ms for the pasty consistency, and between second and third burst was 339.8 ms for water and 322.0 ms for the pasty consistency. Conclusion: The software allowed the visualization of three bursts during the swallowing of healthy individuals, and showed that the swallowing signal in normal subjects is highly variable.
Keywords: Acoustics; Auscultation; Deglutition; Deglutition disorders; Fluoroscopy; Software; acoustics; adult; computer program; dysphagia; female; fluoroscopy; human; male; methodology; middle aged; physiology; signal processing; swallowing; videorecording; Adult; Deglutition Disorders; Female; Humans; Male; Middle Aged; Signal Processing, Computer-Assisted; Video Recording; Young Adult